PERANCANGAN VIDEO GAME BOROBUDUR MELALUI NARASI VISUAL - Putro, Agus Tukiyanto; Putra, Ricky Widyananda (Universitas Budi Luhur, 2024)
The design of the Borobudur video game started from problems the creator encountered related to the lack of historical understanding among teenagers regarding cultural heritage sites. This creation aims to provide an educational interactive experience for teenagers aged 17-22 years related to the history of Borobudur Temple. In designing the video game, the creator used creative methods in the form of observations and interviews with vulnerable teenagers aged 17-22 years. Then the theory used in the work uses the UI & UX Design approach. The discussion in this creation is related to the visual form in video games by referring to the visual narrative that is created. The creator's hope in this game is that educational messages, especially those related to preserving cultural heritage, can be one of the concepts when designing the game.